Project Hope and the Hope School System in China - Wang, Samuel C. (Education Policy Analysis Archives, 1999)
I investigate the creation, development, contributions and limits of Project Hope, a huge government-endorsed education project seeking non-governmental contributions to overcome educational inadequacy in poverty-stricken rural communities in transitional China. By reexamining the composition of sponsored students, the locations of Hope Primary Schools and non-educational orientations for building and expanding schools, I argue that Project Hope and its Hope School system have not contributed to educational access, equality, equity, efficiency and quality as it should have. Poverty-reduction-oriented curriculum requirements in Hope Primary Schools are theoretically misleading and realistically problematic.